2017
DOI: 10.17140/phoj-2-117
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity Prevalence in Young Children Living in Athens

Abstract: Background: The last decades, the epidemiological dimensions of childhood obesity are of major concern worldwide. Given its long-term health consequences, research findings regarding overweight and obesity prevalence in young children are valuable if policies against childhood obesity are to be planned and implemented. As Greece, is one of the countries facing the problem of obesity, the aim of the present study was to assess overweight and obesity status in young children living in the capital of Greece, Athe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
(97 reference statements)
1
0
0
Order By: Relevance
“…The prevalence of childhood overweight and obesity in the studied sample was high (i.e., 26.7%). This is in line with the prevalence of overweight/obesity in a Greek sample presented by Afthentopoulou et al (2017) which was approximately 26%. However, it is significantly lower than the prevalence reported by the Greek Childhood Obesity study (i.e., 41.2%) conducted on similar aged students (Farajian et al, 2011) as well as the combined prevalence of overweight and obesity revealed by a meta-analysis in Greek children, aged 1–12 years which was 34.0% (Kotanidou et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of childhood overweight and obesity in the studied sample was high (i.e., 26.7%). This is in line with the prevalence of overweight/obesity in a Greek sample presented by Afthentopoulou et al (2017) which was approximately 26%. However, it is significantly lower than the prevalence reported by the Greek Childhood Obesity study (i.e., 41.2%) conducted on similar aged students (Farajian et al, 2011) as well as the combined prevalence of overweight and obesity revealed by a meta-analysis in Greek children, aged 1–12 years which was 34.0% (Kotanidou et al, 2013).…”
Section: Discussionsupporting
confidence: 88%